2016
DOI: 10.1111/jce.13020
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Level But Not High‐Level Baroreceptor Stimulation Inhibits Atrial Fibrillation in a Pig Model of Sleep Apnea

Abstract: LL-BRS suppressed NTP-induced AERP-shortening and AF-inducibility. By contrast HL-BRS further perpetuated NTP-induced AERP-shortening and increased AF-inducibility. These findings support only the use of LL-BRS as a novel therapeutic modality to treat AF in OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Linz et al demonstrated that renal denervation suppressed OSA‐induced atrial ERP shortening and increased AF inducibility. Low‐level baroreceptor stimulation, which also modulates autonomic balance, inhibited AF in a pig model of OSA . These studies indicate that the modulation of autonomic remodeling inhibits OSA‐induced AF inducibility.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Linz et al demonstrated that renal denervation suppressed OSA‐induced atrial ERP shortening and increased AF inducibility. Low‐level baroreceptor stimulation, which also modulates autonomic balance, inhibited AF in a pig model of OSA . These studies indicate that the modulation of autonomic remodeling inhibits OSA‐induced AF inducibility.…”
Section: Discussionmentioning
confidence: 59%
“…OSA can shorten the atrial effective refractory period (ERP) and increase the inducibility of AF, which are strong triggers for AF . Previous studies focused on the electrophysiological, sympathovagal, and neurohumoral properties of OSA‐induced AF. However, these studies did not conclusively define a mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we are the first to investigate the neuromodulatory effect of SCS on extrinsic cardiac nerve stimulation on atrial electrophysiology. We found that (a) SCS heightened the role of the vagus nerve and Previous studies have shown that high-level VNS, high-level SGS, and high-level baroreceptor stimulation facilitate AF induction and aggravate electrical remodeling in the atrium 16 and pulmonary veins. [17][18][19] On the other hand, low-level VNS, low-frequency VNS, low-level baroreceptor stimulation, or low-level SCS significantly prolonged the atrial ERP and reduced AF burden and inducibility.…”
Section: Discussionmentioning
confidence: 75%
“…[17][18][19] On the other hand, low-level VNS, low-frequency VNS, low-level baroreceptor stimulation, or low-level SCS significantly prolonged the atrial ERP and reduced AF burden and inducibility. 11,16,20 These results indicate that different intervention model on the extrinsic cardiac nerve has different effects on atrial electrophysiology and AF vulnerability. Cardinal et al 21 During VNS or SGS, the inducibility of AF is more easily than at baseline.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation